Recent advances in matrix‐assisted laser desorption/ionisation mass spectrometry imaging (MALDI‐MSI) for in situ analysis of endogenous molecules in plants. Issue 4 (17th April 2018) - Qin, Liang; Zhang, Yawen; Liu, Yaqin; He, Huixin; Han, Manman; Li, Yanyan; Zeng, Maomao; Wang, Xiaodong
Abstract: Introduction: Mass spectrometry imaging (MSI) as a label‐free and powerful imaging technique enables in situ evaluation of a tissue metabolome and/or proteome, becoming increasingly popular in the detection of plant endogenous molecules. Objective: The characterisation of structure and spatial information of endogenous molecules in plants are both very important aspects to better understand the physiological mechanism of plant organism. Methods: Matrix‐assisted laser desorption/ionization mass spectrometry imaging (MALDI‐MSI) is a commonly‐used tissue imaging technique, which requires matrix to assist in situ detection of a variety of molecules on the surface of a tissue section. In previous studies, MALDI‐MSI was mostly used for the detection of molecules from animal tissue sections, compared to plant samples due to cell structural limitations, such as plant cuticles, epicuticular waxes, and cell walls. Despite the enormous progress that has been made in tissue imaging, there is still a challenge for MALDI‐MSI suitable for the imaging of endogenous compounds in plants. Results: This review summarises the recent advances in MALDI‐MSI, focusing on the application of in situ detection of endogenous molecules in different plant organs, i.e. root, stem, leaf, flower, fruit, and seed. Conclusion: Further improvements on instrumentation sensitivity, matrix selection, image processing and sample preparation will expand the application of MALDI‐MSI in plant research. Abstract : Matrix‐assisted laser desorption/ionisation mass spectrometry imaging (MALDI‐MSI) is a novel label‐free molecular imaging technique that provides new insights into the in situ analysis of endogenous molecules in plant tissue sections.